THE INFLUENCE OF THE GINI RATIO, GOVERNMENT EXPENDITURE, EDUCATION LEVEL AND ZIS (ZAKAT, INFAQ, ALMS) ON POVERTY IN 34 PROVINCES INI INDONESIA IN 2020-2023 - Ariyani, Diyah; Nafisyah, Dhurotun (Diponegoro Journal of Islamic Economics and Business, 2024)
Indonesia is a country that has a problem with its poverty level. In Indonesia, poverty is a social problem that has existed for a long time. However, poverty in Indonesia has experienced a continuing downward trend, although the decline has been slow. This study aims to determine the effect of the Gini ratio, government spending, education level and ZIS (Zakat, Infaq and Sadaqah) on poverty levels in 34 provinces in Indonesia. The method used is multiple linear regression, namely panel data with 136 observations for 4 years starting from 2020 to 2023 using data analysis tools in the form of eviews 10. Based on this research, the results obtained are that the gini ratio variable has a positive and significant effect on the poverty rate in 34 provinces in Indonesia, government spending has a positive and insignificant effect on the poverty rate in 34 provinces in Indonesia, the level of education has a negative and significant effect on the poverty rate in 34 provinces in Indonesia, ZIS has a positive and insignificant effect on the poverty rate in 34 provinces in Indonesia.